Optimization of Pre-Neutralized Red Palm Olein-canola Oil Emulsion Gel as Animal Fat Replacer for Comminuted Meat Product Using Response Surface Methodology (Faculty of Animal Science Universitas Brawijaya, 2022)
Red palm olein, which is rich in Î² carotene, has the potential as an animal fat replacer for the formulation of healthy processed meat products. However, it is mainly composed of saturated fatty acid, which should be reduced by combining it with unsaturated fatty acid-rich vegetable oil. Canola oil was mixed with red palm olein in order to get the benefits from both. The formulation of an emulsion gel made up of red palm olein and canola oil at 30/70 (w/w) was optimized using a response surface methodology. Soy protein isolate (SPI), mono and diglycerides of fatty acids (emulsifier E471, EMS), and inulin (INL) were selected as stabilizer and emulsifier in aqueous phase. Based on formula optimization and validation of gel emulsion ability in the comminuted meat model system, it was concluded that the addition levels of SPI, EMS, and INL required to form gel emulsions with optimal ability to produce comminuted meat products were 5.33%, 0.53% and 3.98% (w/w), respectively.